Development and validation for the simultaneous quantification of Montelukast and Levocetirizine by UV, RP -HPLC and HPTLC methods in tablets - N.Ramesh Kumar; V. Vaidhyalingam (International Journal of Pharmacy and Analytical Research, 2020)
The present study was aim to develop and validate a UV, HPLC and HPTLC methods for simultaneous estimation of montelukast and levocetirizine in tablet dosage form. Linearity was observed for levocetirizine and montelukast in all the methods. Percent recoveries obtained for both the drugs were 99-100%. The percentage RSD for precision and accuracy of the method was found to be less than 2% as per the ICH these methods. The percentage purity thus found is 99.02% and 100.04% for montelukast and levocitirizine. A simple, selective, linear, precise, and accurate UV, HPTLC and RP-HPLC method was developed and validated for the simultaneous estimation of montelukast and levocetrizine in its bulk and liquid dosage form. The method was validated according to the ICH guidelines with respect to specificity, linearity, accuracy, precision, robustness and ruggedness. The methods were developed successfully it is applied for the analysis of simultaneous estimation of montelukast and levocetirizine in tablet dosage form.